The Effect of Social Media Marketing on Repurchase Intention: Mediating Roles of Satisfaction and Brand Image - Fendika Ilvan Jazula; Mugiono; Ikhtiara Kaideni Isharina (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid expansion of e-commerce in Indonesia, driven by platforms like Shopee, underscores the critical role of social media marketing in building customer loyalty amid intense competition. Grounded in the Theory of Planned Behavior, this study aims to investigates the direct and indirect effects of social media marketing on repurchase intention, with brand image and satisfaction as mediators. A quantitative approach was applied, surveying 351 Shopee customers aged 17 and above who had made multiple purchases in the past six months and engaged with Shopee’s social media. Data were analyzed using Structural Equation Modeling Partial Least Squares. Results indicate that social media marketing, brand image, and satisfaction all positively and significantly affect repurchase intention. Moreover, social media marketing strengthens brand image and satisfaction, which partially mediate its impact, with satisfaction emerging as the stronger mediator. This study contributes to e-commerce literature by clarifying the mechanisms through which social media marketing fosters repeat purchases. Practically, it suggests that Shopee should invest in engaging content and high-quality service to reinforce loyalty, offering actionable insights for e-commerce platforms competing in dynamic markets.